Visum Et Repertum Dalam Proses Pembuktian Perkara Pidana Pemerkosaan - Ardhya Fauzah Fardhyanti; Puti Priyana (Widya Yuridika, 2022)
Visum et Repertum is written by a doctor according to what he saw and found on living, corpses, or physical evidence and then analyzed based on his knowledge. Doctors are given the whole task at the time of making the visum et repertum as organizers in the field in facilitating the smooth running of the investigation, helping prosecutors determine the direction of the indictment, and making it easier for judges to find material truth in making decisions. This type of research is normative law research, a method to find the truth based on literature using legal literature materials, applicable laws and regulations, official documents, and other media to obtain data or theories related to the research problem product. The nature of the research used is descriptive, which seeks to describe the object or subject under study following what it is. Although, based on the Visum Et Repertum Number RSUPP.331/VER/61/XII/2020 dated December 10, 2020, no injuries were found, the Panel of Judges did not have to stick to the evidence for the Visum Et Repertum. Because experts or doctors are just ordinary people who are likely to make mistakes, judges are not required to follow the opinion of the experts or doctors if it is not follow what they believe. The power of Visum et Repertum is considered necessary in proving the crime of rape because it can the truth be found whether the crime occurred. However, Visum et Repertum cannot stand alone and must be supported by other valid evidence. For this reason, the author hopes that experts in investigations hope that victims of rape crimes must be neutral following the doctor's oath of office.